The Common Haplotype GATGACA in Surfactant-Protein B Gene Is Protective for Respiratory Distress Syndrome in Preterm Neonates - Mikolajcikova, Silvia; Lasabova, Zora; Holubekova, Veronika; Skerenova, Maria; Zibolenova, Jana; Matasova, Katarina; Zibolen, Mirko; Calkovska, Andrea (Frontiers in Pediatrics, 2022)
Background: Respiratory distress syndrome (RDS), a disorder of primary surfactant deficiency resulting in pulmonary insufficiency, remains a significant problem for preterm neonates. Associations between genetic variants of surfactant proteins and RDS have been reported but haplotypes of surfactant protein B gene (SFTPB) have not been studied. The aim of the study was to prove the hypothesis that certain haplotypes of SFTPB may be protective or risk factors for RDS. Methods: The study was performed with 149 preterm infants, born <34 weeks of gestation, with 86 infants with mild RDS or without RDS (control group) and 63 infants with severe RDS (patient group). RDS was considered severe if multiple doses of exogenous surfactant and/or mechanical ventilation within the first 72 hours of life were needed. The venous blood sample was used for analysis of gene polymorphisms associated with RDS, genotyping and haplotype estimation. Multivariate logistic regression analysis and the odds ratio were calculated to detect the contribution of the studied variables to the development of RDS. Results: A new association of common single nucleotide polymorphism (SNP) rs2304566 with RDS in premature infants was detected. Analysis of rs2304566 polymorphisms using logistic regression model showed that there are two significant predictors inversely related to the occurrence of RDS (Apgar score at 5th minute, CT and TT genotype in rs2304566 polymorphism). Gestational age, birth weight and sex have border significance. Moreover, in the patient group the frequency of GATGACA haplotype in SFTPB gene was lower (p=0.037) and GATGGCA haplotype was higher (p=0.059) in comparison with the control group. Conclusion: The common haplotype GATGACA of the SFTPB gene can be protective for RDS in preterm infants. The trend of higher frequency of GATGGCA in SFTPB gene in infants with severe RDS suggests that this haplotype may be a risk factor for RDS susceptibility.